RNA Drug Delivery Using Biogenic Nanovehicles for Cancer Therapy - Li, Nuannuan; Sun, Yiying; Fu, Yuanlei; Sun, Kaoxiang (Frontiers in Pharmacology, 2021)
RNA-based therapies have been promising method for treating all kinds of diseases, and four siRNA-based drugs and two mRNA-based drugs have been approved and are on the market now. However, none of them is applied for cancer treatment. This is not only because of the complexity of the tumor microenvironment, but also due to the intrinsic obstacles of RNAs. Until now, all kinds of strategies have been developed to improve the performance of RNAs for cancer therapy, especially the nanoparticle-based ones using biogenic materials. They are much more compatible with less toxicity compared to the ones using synthetic polymers, and the most widely studied biogenic materials are oligonucleotides, exosomes, and cell membranes. Particular characteristics make them show different capacities in internalization and endosomal escape as well as specific targeting. In this paper, we systematically summarize the RNA-based nano-delivery systems using biogenic materials for cancer therapy, and we believe this review will provide a valuable reference for researchers involved in the field of biogenic delivery and RNA-based therapies for cancer treatment.